PERAN KREDIT DARI KOPERASI SERBA USAHA (KSU) â€œARTHA SUKSESâ€ TERHADAP PERKEMBANGAN USAHA MIKRO YANG MENJADI ANGGOTANYA DI KOTA SEMARANG - Mustofa, Pipit; Hendra Setiawan, Achma (Diponegoro Journal of Economics, 2013)
Microâ€™s Enterprises always present in the countryâ€™s economy, because they have a role in supporting the regional and national economy. In Semarang, the problems faced by the Micro Enterprises are the problem of capital, which Â Micro-entrepreneurs do not have sufficient working capital to run the business.This research tried to know differences in the development of the Micro Enterprises as a member of Business Multipurpose Cooperative (KSU) Artha Sukses between: before and after getting credite assistance from Business Multipurpose Cooperative (KSU) Artha Success in terms of capital, labor, sales turnover, and profit. The object of this research are 70 Micro Enterprises which get a credite from KSU Artha Success in Semarang. The methods analysis consist of validity and reliability test, and also Wilcoxon sign rank statistical test.Based on the results of Wilcoxon sign rank statistical test, obtainedÂ venture capital in the variable p-value of 0.000 (0.000 <0,05). It means there is a significant increase in venture capital variable that is equal to 144.23%. In labor variables obtained p-value of 0.000 (0.000 <0,05). It means that there is significant improvement in the labor variable that is equal to 12.5%. In sales turnover variables obtained p-value of 0.000 (0.000 <0.05) it means there is a significant increase in variable sales turnover of 123.83%. On variable profits obtained p-values of 0.000 (0.000 <0,05). It means that there is a significant increase in variable profit is equal to 133.11%.